ANALISIS KEMAMPUAN PEMAHAMAN DALAM KONSEP BENTUK ALJABAR KELAS VII DI TINJAU DARI GAYA BELAJAR PESERTA DIDIK - Avelia Gisela Denggot (LPPM Universitas Bina Bangsa, 2023)
This study makes use of qualitative techniques for the purpose of description. The purpose of this study is to identify the various ways in which students comprehend the idea of algebraic forms. In this study, three seventh-graders from SMP N 4 Tondano represented the different types of learning styles (visual, kinesthetic, and audiotorial). Students were asked about their preferred learning methods, with one representative from each of the three learning styles (visual, kinesthetic, and audiotorial) being chosen as research subjects. This study's findings indicate that (1) subjects with a visual learning style performed better on tests and interviews, particularly when it came to providing answers that were both correct and presented in different ways. (2) students who learn best through movement but who aren't as methodical as others. The test results showed this, but he gave a reasonable explanation during the interview. Auditory learners, number three. This is evident from the interview and test results, which provide an excellent explanation for question 1 but fail to adequately address question 2